On Farm Emergency Slaughter and Emergency Killing of Acutely Injured Cattle: Analysis of Guidelines From Five Jurisdictions - McDermott, Paul; McKevitt, Aideen; Hanlon, Alison (Frontiers in Veterinary Science, 2022)
Background: In July 2009, the Farm Animal Welfare Advisory Council (FAWAC) in the Republic of Ireland published Animal Welfare Guidelines for the Management of Acutely Injured Animals on Farm in support of a new Irish regulation designed to permit on-farm emergency slaughter (OFES) of cattle. The purpose of this study was to evaluate the FAWAC guidelines, to determine if they remain fit for purpose by comparing them with five guidelines on the management of acutely injured cattle from four jurisdictions purposively selected because of their relevance to OFES, and to represent geographical and organisational diversity; The United Kingdom, Australia, New Zealand and British Columbia/Canada. Methodology: Content and Thematic Analysis were used to compare the incidence and frequency of themes in the six guidelines using NVIVO 12. Results: Humane killing and slaughter of animals and the prevention of unnecessary suffering at time of killing were emphasised in all guidelines. Thematic Analysis identified seven primary themes (‘parent nodes’): animal welfare; decision tree; certification; legislation; stakeholders; transport and; veterinary ethics. Parent nodes encompassed 26 secondary themes (‘child nodes’) including casualty slaughter, on-farm emergency slaughter, euthanasia, unnecessary suffering, animal owner, private veterinary practitioner, official veterinarian and fitness for transport. Guidelines outlined stakeholders’ roles in relation to all aspects of managing acutely injured cattle. Results showed similarities between FAWAC, the British Cattle Veterinary Association and the British Columbian/Canadian guidelines in relation to OFES as a method to address acutely injured cattle. OFES is not allowed in Australia or New Zealand as a method of managing acutely injured cattle. Conclusions: Animal welfare guidelines play a pivotal role in informing all stakeholders involved in the management of acutely injured cattle. Guidelines vary from prescriptive standard operating procedures on actions that should be undertaken for food safety reasons, to descriptive guidance upholding practicalities in relation to equipment and methods to be used in managing acutely injured cattle not meant for human consumption. The FAWAC guidelines remain substantially relevant today and consistent with other welfare guidelines published in the jurisdictions that formed part of the study. However, they need to be reviewed to align with current regulations.